New perspectives in the reconstruction of the way of life of the shell mound builders: a multidisciplinary approach - Scheel-Ybert, Rita (2023)
The assemblage of original data and literature reviews in a mostly new multidisciplinary approach in Brazilian archaeology provided a base for the better understanding of the shell mound builder society. Anthracological analysis allowed palaeoecological reconstruction of the coastal environment and provided information about firewood economy and diet in this society. Palaeopathological analyses revealed important aspects of the lifestyle of shell mound builders and their relationship with the environment. The combination of results of these two disciplines, associated to lithic analyses, pointed to economic and subsistence spectra way larger than considered so far, confirmed the importance of plants to this society, and supplied more solid bases to the debate concerning management and plant cultivation.